Lower Mortality in Very Elderly Patients and Heart Failure Patients Admitted to the Hospital Having High Blood Pressure - Lindstedt, Isak; Edvinsson, Lars; Edvinsson, Marie-Louise (Cardiology and Cardiovascular Medicine, 2019)
Introduction: How to handle blood pressure in very elderly patients (> 80 years) is still debatable. Many are frail, dependent, and susceptible to drug interactions, and have not been included in blood pressure trials. Thus, how blood pressure levels in these patients predict future events remains unclear. Methods: We studied a cohort of 339 elderly patients with a mean age of 83 years that visited the emergency department and were subsequently admitted into the hospital. We divided the cohort into two groups: 144 patients with blood pressure ≥ 140/90 mm Hg (HBP-group) and 195 patients with blood pressure < 140/90 mm Hg (NBP-group). Mean blood pressure in the HBP-group was 158/83 mm Hg and 122/70 mm Hg in the NBP-group. Furthermore, we also did a subgroup analysis on a total of 178 patients with heart failure, totaling 69 with high blood pressure with a mean of 155/85 mm Hg (HBPHF-group) and 109 without high blood pressure with a mean of 119/71 mm Hg (NBPHFgroup). Results: After 6 months 20 patients were dead in the HBP-group compared to 54 patients in the NBP-group (p < 0.01). In the subgroup analysis, 6 patients were dead in the HBPHF-group and 26 patients were dead in the NBPHF-group after 6 months (p = 0.01). Conclusions: We found that very elderly patients in general but also patients with heart failure in particular that presented with high blood pressure when enrolling into the hospital had significantly lower 6-month mortality than very elderly with normal blood pressure.